Lots of geometrical coincidences

Geometry Level 5

In A B C \triangle ABC , A B = A C AB=AC . Now a point D D lies on A C AC so that A B = B D AB=BD and a point E E satisfies A D = B E AD=BE as well as A C = C E AC=CE . Interestingly, points B B , E E and D D are collinear. If A B C = p π q \angle ABC=\frac{p\pi}{q} radians where p p and q q are coprime positive integers, p + q = ? p+q=\boxed{?}


The answer is 23.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Noel Lo
Aug 1, 2017

Let A B C = θ \angle ABC=\theta . We add a point F F such that A C AC is parallel to B F BF and A B = B F AB=BF . Considering that A B = B D AB=BD , it follows that B A D = B D A = π A B D 2 \angle BAD=\angle BDA=\frac{\pi-\angle ABD}{2} . Moreover, A C AC being parallel to B F BF tells us that B A D + A B F = π \angle BAD+\angle ABF=\pi or B A D + A B D + D B F = π \angle BAD+\angle ABD+\angle DBF=\pi . Therefore D B F = π A B D B A D = π A B D π A B D 2 = π A B D 2 = B A D \angle DBF=\pi-\angle ABD-\angle BAD=\pi-\angle ABD-\frac{\pi-\angle ABD}{2}=\frac{\pi-\angle ABD}{2}=\angle BAD .

As given in the question, A D = B E AD=BE and we stipulate that A B = B F AB=BF . Considering that B A D = F B E \angle BAD=\angle FBE , we conclude that B A D \triangle BAD is congruent to F B E \triangle FBE employing S A S SAS congruence. This tells us that A B D = B F E = B F C C F E = B A D C F E \angle ABD=\angle BFE=\angle BFC-\angle CFE=\angle BAD-\angle CFE . Note that B F C = B A D \angle BFC=\angle BAD being opposite angles in rhombus A B F C ABFC .

Considering also that B A D = π A B D 2 \angle BAD=\frac{\pi-\angle ABD}{2} :

B A D = π ( B A D C F E ) 2 \angle BAD=\frac{\pi-(\angle BAD-\angle CFE)}{2}

2 B A D = π ( B A D C F E ) 2\angle BAD=\pi-(\angle BAD-\angle CFE)

2 B A D + B A D C F E = π 2\angle BAD+\angle BAD-\angle CFE=\pi

( 2 + 1 ) B A D = π + C F E (2+1)\angle BAD=\pi+\angle CFE

3 B A D = π + C F E 3\angle BAD=\pi+\angle CFE

Considering that A B = A C AB=AC and hence A C B = A B C \angle ACB=\angle ABC in A B C \triangle ABC , B A D = B A C = π A B C A C B = π 2 A B C = π 2 θ \angle BAD=\angle BAC=\pi-\angle ABC-\angle ACB=\pi-2\angle ABC=\pi-2\theta . Then:

3 ( π 2 θ ) = π + C F E 3(\pi-2\theta)=\pi+\angle CFE

3 π 6 θ = π + C F E 3\pi-6\theta=\pi+\angle CFE

6 θ + C F E = 2 π 6\theta+\angle CFE=2\pi

A final observation to make is this:

  • Considering that A B = B D AB=BD , A B = A C AB=AC and that A C = C E AC=CE as given in the question, it then follows that B D = C E BD=CE and C E = E F CE=EF .
  • Considering that A B = A C = B F AB=AC=BF and that A C AC is parallel to B F BF , we see that A B F C ABFC is a rhombus so that C F = A B = A C = B F CF=AB=AC=BF . Then considering that A C = C E AC=CE , C F = A C CF=AC means that C E = C F CE=CF .

Combining C E = C F CE=CF and C E = E F CE=EF , C E F \triangle CEF is equilateral with C E = C F = E F CE=CF=EF . This means C E F = E C F = C F E = π 3 \angle CEF=\angle ECF=\angle CFE=\frac{\pi}{3} . Therefore:

6 θ + π 3 = 2 π 6\theta+\frac{\pi}{3}=2\pi

6 θ = ( 6 1 ) π 3 6\theta=\frac{(6-1)\pi}{3}

6 θ = 5 π 3 6\theta=\frac{5\pi}{3}

θ = 5 π 6 × 3 \theta=\frac{5\pi}{6\times 3}

θ = 5 π 18 \theta=\frac{5\pi}{18}

So p + q = 5 + 18 = 23 p+q=5+18=\boxed{23}

.

Yee-Lynn Lee
Jul 6, 2019

For simplicity, take A B = 1 AB = 1 . Also, let D C E = θ ∠DCE = θ . Since B D = A B = A C BD = AB = AC and A D = B E AD = BE , E D = B D B E = A C A D = C D ED = BD - BE = AC - AD = CD , meaning that C D E △CDE is isosceles. Then, D E C = θ ∠DEC = θ as well, and by the External Angle Theorem, B D A = 2 θ ∠BDA = 2θ .

We use the fact that A D + D C = A C = 1 AD + DC = AC = 1 and write A D AD and D C DC in terms of θ θ to obtain an equation in θ θ .

Because B A D △BAD is isosceles, the perpendicular from B B bisects A D AD , so A D = 2 B D cos 2 θ = 2 cos 2 θ AD = 2 BD \cos{2θ} = 2 \cos{2θ} . Likewise, since D C E △DCE is isosceles, the perpendicular from D D bisects C E CE , so D C = C E 2 cos θ = 1 2 cos θ DC = \frac{\frac{CE}{2}}{\cos{θ}} = \frac{1}{2 \cos{θ}} .

Then, we have that 1 2 cos θ + 2 cos 2 θ = 1 \frac{1}{2 \cos{θ}} + 2 \cos{2θ} = 1 .

Using the identity cos 2 θ = 2 cos 2 θ 1 \cos{2θ} = 2 \cos^2{θ} - 1 , multiplying both sides by 2 cos θ 2 \cos{θ} , simplifying, this becomes 8 cos 3 θ 6 cos θ + 1 = 0 8 \cos^3{θ} - 6 \cos{θ} + 1 = 0 .

Using the identity cos 3 θ = 4 cos 3 θ 3 cos θ \cos{3θ} = 4 \cos^3{θ} - 3 \cos{θ} , we get 2 cos 3 θ + 1 = 0 2 \cos{3θ} + 1 = 0 , so θ = 2 π 9 θ = \frac{2\pi}{9} (any larger θ θ that satisfies the equation causes 2 θ to be greater than 90 ° 90° , which doesn't work as the sum of the internal angles of B A D △BAD is greater than 4 θ ).

Finally, since A B C △ABC is isosceles with B A C = θ ∠BAC = θ , A B C = π 2 θ = 5 π 18 ∠ABC = \frac{\pi}{2} - θ = \frac{5\pi}{18} , so our answer is 5 + 18 = 23 5 + 18 = \boxed{23} .

K T
Jun 19, 2019

We have some isoscelese triangles:

  • because A B = A C AB=AC we have A B C = A C B = β \angle ABC = \angle ACB = β , so that B A C = α = π 2 β \angle BAC = α = π-2β
  • because A B = B D AB=BD we have A D B = α \angle ADB = α , so that C D E = π α = 2 β \angle CDE=π-α=2β
  • because D E = C D DE=CD we have D C E = D E C = γ \angle DCE= \angle DEC = γ

Using the fact that the sum of angles in a triangle add up to π, we can easily find that

  • α = π 2 β α=π-2β
  • γ = 1 2 π β γ=\frac{1}{2}π-β
  • δ = A B D = π 2 α = 4 β π δ=\angle ABD = π-2α = 4β-π

Scale the diagram such that A B = 1 AB=1 . The cosine rule c 2 = a 2 + b 2 2 a b cos φ c^2=a^2+b^2-2ab \cos φ can be applied to A B D \bigtriangleup ABD , so that, setting x = A D x=AD , x 2 = 2 2 cos ( 4 β π ) = 2 + 2 cos 4 β x^2 = 2-2\cos (4β-π) = 2+2\cos 4β Via the identity cos 2 t = 2 cos 2 t 1 \cos 2t = 2\cos^2 t -1 setting t = 2 β t=2β , we get x 2 = 4 cos 2 β x = 2 cos β x^2 = 4\cos^ 2β \Rightarrow x=|2\cos β| , and because α , δ > 0 1 4 π < β < 1 2 π cos 2 β < 0 α,δ>0 \Rightarrow \frac{1}{4}π < β < \frac{1}{2}π\Rightarrow \cos 2β < 0 , this means that x = 2 cos 2 β x=-2\cos 2β The cosine rule can also be applied to C D E \bigtriangleup CDE , so that 1 2 = ( 1 x ) 2 ( 2 2 cos 2 β ) 1^2 =(1-x)^2(2-2\cos 2β) Substituting x x with 2 cos 2 β -2\cos 2β , we obtain 8 cos 3 2 β + 6 cos 2 β + 1 = 0 -8\cos^3 2β+6 \cos 2β + 1 = 0 Because of the identity cos 3 t = 4 cos 3 t 3 cos t \cos 3t = 4\cos^3 t - 3 \cos t and setting t = 2 β t=2β , we can rewrite this as 1 2 cos ( 6 β ) = 0 1-2 \cos(6β)=0 which solves to β = 6 k ± 1 18 π ( k Z ) β= \frac{6k \pm 1}{18}π \text{ } (k \in \mathbb{Z})

To satisfy both 0 < x < 1 0<x<1 and 0 < β < π 0<β<π we need 1 4 π < β < 1 3 π \frac{1}{4}π < β < \frac{1}{3}π , so that only β = 5 18 π = 50 ° β= \frac{5}{18}π=50° is in this range and the answer is 5 + 18 = 23 5+18= \boxed{23} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...